2021
DOI: 10.1186/s12887-021-02584-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of neural tube defects and their risk factors within a cohort of Moroccan newborn infants

Abstract: Background Neural tube defects (NTDs) are a group of birth defects that result from a partial or complete failure of the neural tube to close during embryogenesis. Their prevalence varies between 0.5 to 2 per 1000 births in countries without folic acid supplementation. The aim of our study is to assess the NTDs incidence and describe the risk factors within Moroccan newborn infants. Method This is a descriptive study over a period of 5 and a half y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 43 publications
3
20
1
Order By: Relevance
“…Our research also found that all mothers did not received folic acid supplementation throughout their pregnancy. This finding is consistent with studies conducted in Addis Ababa, Ethiopia, and Morocco [10,13,23]. This could be due to is lack of preconception care in the country as well as a lack of media coverage on promotion of preconception of folic acid supplementation.…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…Our research also found that all mothers did not received folic acid supplementation throughout their pregnancy. This finding is consistent with studies conducted in Addis Ababa, Ethiopia, and Morocco [10,13,23]. This could be due to is lack of preconception care in the country as well as a lack of media coverage on promotion of preconception of folic acid supplementation.…”
Section: Plos Onesupporting
confidence: 91%
“…Anencephaly was found to be the most common type of NTD (48.1%), followed by spina bifida (22.6 percent), which is consistent with findings from a study conducted at three teaching hospitals in Addis Ababa, Ethiopia [13], in Tigray region, Ethiopia [11], Amhara region, Ethiopia [19], Bale zone Oromia, Ethiopia [20], Gujarat hospital, India (26%) [21], South west Iran (86.8%) [22], in Morocco [23], and in Nigeria [24]. These findings contradict the findings of studies conducted at Tikur Anbessa, Gandhi Memorial, and Ethio-Sewdish Hospitals in…”
Section: Plos Onesupporting
confidence: 83%
“…In our study, half of the NTD cases (three cases) had multiple malformations, one anencephaly associated with cleft lip and palate, one spina bifida associated with congenital atresia of the rectum and anus, and one encephalocele with craniotabes (Supplementary Table 3), which demonstrate the importance of improving the prenatal diagnosis to reduce fetal BDs. Together, this study suggest that the prevention and control strategies implemented by the Ministry of Health should be further strengthen by enforcing folic acid supplementation, increasing women's awareness of BDs, providing more adequate medical care for pregnancy women, such as prenatal diagnosis (22). Another highlight of this study was that we classified the common BDs according to their etiology.…”
Section: Discussionmentioning
confidence: 91%
“…Anencephaly, spina bifida and encephalocele, which are the three main types of neural tube defects (NTDs) ( 5 , 22 , 23 ). Mandatory folic acid supplementation is highly likely to be responsible for the NTDs being one of the least common BDs, which had also been observed in our study and other reports ( 3 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation